2012
DOI: 10.1038/nature11567
|View full text |Cite|
|
Sign up to set email alerts
|

Optical-field-induced current in dielectrics

Abstract: The time it takes to switch on and off electric current determines the rate at which signals can be processed and sampled in modern information technology. Field-effect transistors are able to control currents at frequencies of the order of or higher than 100 gigahertz, but electric interconnects may hamper progress towards reaching the terahertz (10(12) hertz) range. All-optical injection of currents through interfering photoexcitation pathways or photoconductive switching of terahertz transients has made it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
577
3
5

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 687 publications
(617 citation statements)
references
References 27 publications
13
577
3
5
Order By: Relevance
“…Generation of high harmonics even for the circularly polarized laser fields is consistent with scattering from neighbouring sites in the crystal. These results open up the possibility of measuring field-induced charge flow 23,24,28,29 and imaging atomic orbitals in solids 30 , which we discuss in the Methods. In analogy to the conventional electron diffraction methods, solidstate HHG allows us to use electrons that are already present in the bulk matter to image the ångström-scale structure of the condensed matter.…”
mentioning
confidence: 99%
“…Generation of high harmonics even for the circularly polarized laser fields is consistent with scattering from neighbouring sites in the crystal. These results open up the possibility of measuring field-induced charge flow 23,24,28,29 and imaging atomic orbitals in solids 30 , which we discuss in the Methods. In analogy to the conventional electron diffraction methods, solidstate HHG allows us to use electrons that are already present in the bulk matter to image the ångström-scale structure of the condensed matter.…”
mentioning
confidence: 99%
“…The reversible field-induced change of absorption in the extreme ultraviolet spectral range was observed by probing the effect of an intense near-infrared field on a thin silica plate using an attosecond pulse of extreme ultra-violet radiation as a probe [9]. A subcycle turn-on of electric current in a dielectric and its manipulation with CEP-stabilized pulses was demonstrated by measuring the residual polarization induced by the laser light [10]. This last effect is most closely related to the topic of this chapter, so it is discussed in more detail in the following section.…”
Section: A Numerical Examplementioning
confidence: 99%
“…1.2(b), an optical field that is strong enough to excite valence-band electrons of a dielectric to its conduction bands is also strong enough to significantly accelerate the created charge carriers, thus driving electric current. One of the most important findings in [10] was that such electric current can be turned on within a fraction of a half-cycle of a short intense laser pulse. This was demonstrated by irradiating a SiO 2 sample placed between two gold electrodes with CEP-stabilized laser pulses (see Fig.…”
Section: Ultrafast Injection and Control Of Current In Dielectricsmentioning
confidence: 99%
See 1 more Smart Citation
“…Related work with solids subjected to strong fields has also shown that the material may be reversibly changed from being a dielectric (insulator) to a semi-metal (conductor) in a femtosecond [9][10][11] .…”
mentioning
confidence: 99%